Reversible addition fragmentation chain transfer‐mediated bioconjugated amphiphilic graft‐block copolymer using dextran, poly (N‐isopropylacrylamide), and poly (vinyl acetate). Issue 19 (17th December 2020) - Das Karmakar, Puja; Shukla, Aparna; Maiti, Pralay; Chatterjee, Soumit; Pal, Sagar
Abstract: RAFT polymerization is a well‐known approach to develop amphiphilic copolymer with less heterogeneity and narrow dispersity. Herein, an amphiphilic bioconjugated graft‐block copolymer (Dextran‐ g ‐(PNIPAAm‐ b ‐PVAc)) using dextran, N ‐isopropyl acrylamide and vinyl acetate has been developed through RAFT polymerization. The chain length of the PVAc block has been varied to obtain the copolymers with different hydrophobic segments. The lower critical solution temperature, critical micelle concentration, and micellar stability of the synthesized copolymers have been studied in details. in‐vitro cytotoxicity, as well as the in vitro release of a hydrophobic drug have been carried out to explore its suitability in the field of biomedical science. The synthesized copolymer has been found to have controlled molecular weight with narrow dispersity. It is cytocompatible toward Human cervical cancer cell line cell lines, can efficiently load a hydrophobic drug‐norfloxacin, and subsequently, release in the sustained manner as manifested from in vitro release study. Abstract :